Regional workshop on sustainable, inclusive management of pastoral ecosystems and their socio-economic potential - AbdelHamied, Hamid (Food and Agriculture Organization of the United Nations, 2022)
The Food and Agriculture Organization of the United Nation’s (FAO) Regional Office for the Near East and North Africa (NENA) has organized a regional workshop on sustainable and inclusive management of pastoral ecosystems and their socio-economic potential in the NENA countries. The event gathered around 70 participants from Algeria, Jordan, Mauritania, Morocco, Saudi Arabia, Sudan and Tunisia with representatives from ministries of agriculture, universities and research sector, and professional pastoral organizations. Several regional and international organizations also attended the workshop, such as the Arab Organization for Agricultural Development, International Union for Conservation of Nature (IUCN), Maghreb Arab Union (UMA) and International Center for Agricultural Research in the Dry Areas (ICARDA). The workshop aimed to present the results of the regional assessment on the current situation of pastoralism, management of pastoral ecosystems and their socio-economic potential. The workshop provided a platform to discuss the future of pastoralism in the region and to come up with a regional roadmap for a harmonized and sustainable management of pastoral resources. Participants noted the lack of a reliable database on pastoral ecosystems, the absence of valorization of the economic, social and environmental values provided by the pastoral resources and inadequate policies and legal framework that need to take into account the traditional management systems and local knowledge hand in hand with the technical and scientific knowledge. Participants recognized FAO’s support to the sustainable management of natural resources including rangelands and pastoralism and encouraged the exchange of experience within the region including the capacity building programme in support to pastoralists and building the capacities of national experts in the valuation of goods and services provided by pastoral ecosystems and requested FAO’s support to facilitate this process.